2016
DOI: 10.1038/ng.3559
|View full text |Cite
|
Sign up to set email alerts
|

Punctuated bursts in human male demography inferred from 1,244 worldwide Y-chromosome sequences

Abstract: We report the sequences of 1,244 human Y chromosomes randomly ascertained from 26 worldwide populations by the 1000 Genomes Project. We discovered more than 65,000 variants, including SNVs, MNVs, indels, STRs, and CNVs. Of these, CNVs contribute the greatest predicted functional impact. We constructed a calibrated phylogenetic tree based on binary SNVs and projected the more complex variants onto it, estimating the numbers of mutations for each class. Our phylogeny reveals bursts of extreme expansions in male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
396
4
19

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 293 publications
(456 citation statements)
references
References 57 publications
27
396
4
19
Order By: Relevance
“…Examination of the Y-chromosomal phylogeny established for these samples using Y-SNP variation (Poznik et al 2016) showed that, as expected, the different copy numbers of TTTY22-CNV were often clustered in branches of the phylogeny, so that the number of mutational events inferred was just 20 (Fig. 2, and see below for further details), nevertheless indicating a relatively high mutation rate compared with SNPs.…”
Section: Population Variation and Phylogeny Of Ttty22-cnvmentioning
confidence: 99%
See 4 more Smart Citations
“…Examination of the Y-chromosomal phylogeny established for these samples using Y-SNP variation (Poznik et al 2016) showed that, as expected, the different copy numbers of TTTY22-CNV were often clustered in branches of the phylogeny, so that the number of mutational events inferred was just 20 (Fig. 2, and see below for further details), nevertheless indicating a relatively high mutation rate compared with SNPs.…”
Section: Population Variation and Phylogeny Of Ttty22-cnvmentioning
confidence: 99%
“…Samples with three copies showed the latter pattern plus a separate, additional fibre-FISH signal, and are described separately below. Finally, 10x Genomics Chromium linked-read data (Zheng et al 2016) were available for samples with one and two copies; the sample with one copy shows uniform distributions of barcode sharing and read depth across both TTTY22-CNV locations, while the sample with two copies shows increased barcode sharing and read depth in IR3 proximal and decreased sharing and depth in IR3 distal (Fig. S2).…”
Section: Validation Of Ttty22-cnvmentioning
confidence: 99%
See 3 more Smart Citations